Innovative surgical approaches for hepatocellular carcinoma - Memeo, Riccardo (World J Hepatol, 2016)
Hepatocellular carcinoma (HCC) is the sixth most common cancer worldwide, with an increasing diffusion in Europe and the United States. The management of such a cancer is continuously progressing and the objective of this paper is to evaluate innovation in the surgical treatment of HCC. In this review, we will analyze the modern concept of preoperative management, the role of laparoscopic and robotic surgery, the intrao-perative use of three dimensional models and augme-nted reality, as well as the potential application of fluore-scence.